Feasibility of Endovascular Recanalization of Occluded Infrapopliteal Drug-Eluting Stents. (June 2014) - Spiliopoulos, Stavros; Theodosiadou, Vasiliki; Fragkos, George; Diamantopoulos, Athanasios; Katsanos, Konstantinos; Siablis, Dimitrios; Karnabatidis, Dimitrios
Purpose: To investigate the safety and feasibility of percutaneous endovascular recanalization of late total occlusions of infrapopliteal drug-eluting stents (DES). Methods: A retrospective study investigated all 408 infrapopliteal stent procedures performed in 367 patients between January 2007 and October 2013 to identify those who underwent percutaneous reintervention for symptomatic infrapopliteal balloon-expandable DES occlusion. The search identified 49 patients with at least one infrapopliteal DES occlusion in 61 (14.9%) of 408 limbs. Seven (14.3%) patients were excluded from the analysis owing to asymptomatic status (n=6) and acute thrombotic occlusion (n=1), leaving 42 patients who underwent endovascular revascularization of occluded stents in 54 limbs. The study's primary outcomes were technical success and complication rates of endovascular recanalization, while secondary outcomes included limb salvage and the identification of factors influencing primary results. Results: Technical success was 90.7% (49/54 procedures). Technical failure was seen only in cases of stent collapse and overlapping native popliteal artery–infrapopliteal stent occlusion. According to Kaplan-Meier analysis, survival was 89.6%, 81.1%, and 73.5% at 1, 2, and 3 years, respectively, while limb salvage rates were 86.1%, 79.3%, and 72.7% at the same time points. There was 1 (1.8%) case of distal embolization. No factors influencing outcomes could be identified. Conclusion: Percutaneous recanalization of infrapopliteal stent total occlusions is safe and feasible. Technical failure was noted in cases of stent deformation occurring at the pedal artery and in overlapping native popliteal artery–infrapopliteal stent occlusion.